En Bloc Resection with the Assistance of Video‐Assisted Thoracoscopy for Left Lower Lung Cancer Invading Thoracic Vertebrae and Rib: A Case Report. Issue 4 (27th November 2017) - Liang, Yun; Liu, Peng; Zhou, Xiao‐gang; Li, Xi‐lei; Lin, Hong; Chen, Nong; Ge, Di; Dong, Jian
Abstract : Lung cancer invading the spine was previously considered unresectable and fatal and, consequently, there are few reports focusing on tumors located in the lower lung lobe and invading the spine. With the development of spinal instrumentation and surgical techniques, and wider acceptance of spondylectomy by surgeons, radical surgical resection has become feasible. Here, we present a case of a male patient with a left lower lung cancer invading thoracic vertebrae who underwent complete resection with sagittal en bloc hemivertebrectomy with video‐assisted thoracoscopy. A 60‐year‐old man complained of left chest pain for 3 months. Chest computed tomography and thoracic vertebrae magnetic resonance image revealed that a tumor in the left lower lung lobe had invaded the seventh and eighth thoracic vertebrae and the eighth rib. As no lymph node or distant metastasis was detected by positron emission tomography‐computed tomography, the patient was diagnosed with left lower lung cancer directly invading the seventh and eighth thoracic vertebrae and the eighth rib (T4N0M0, stage IIIA) instead of metastasizing to the thoracic vertebrae. An en bloc resection of the lung tumor and the involved vertebrae was performed by a thoracic surgeon and orthopaedic surgeon with video‐assisted thoracoscopy. Six months after the operation, there was no evidence of local recurrence, and the patient had recovered well. En Bloc resection with video‐assisted thoracoscopy for lung cancer invading thoracic vertebrae is a safe and feasible surgical method. This method can significantly improve the safety and convenience of this type of surgery.